Evaluation of medication administration errors in geriatric patient in medical wards in two government hospitals of Kabul, Afghanistan / Jawed Ahmad Oneeb Abdul Mohammad - Abdul Mohammad, Jawed Ahmad Oneeb (2018)
Evaluation of Medication Administration Errors (MAEs) among geriatric inpatients in the local setting requires more extensive investigation and time. There are not enough academic sources on the epidemiology of MAEs and patients' outcomes among geriatric inpatients. Hence, a prospective study was conducted to determine the prevalence, contributing factors, and effects of MAEs on patients' outcomes in geriatrics. This study was carried out in two government hospitals of Kabul city, Afghanistan. In Ibn Sina Emergency hospital, total number of observations was 456, and MAEs were calculated for 204 cases (44.7%). The most common type of MAEs was the wrong time (67.6%) followed by missed dose (15.7%), wrong concentration (5.0%), with 8 errors (3.9%) caused patient harm but did not need interventions. Multivariate analysis of variables indicates that the route of administration (adjusted OR: 4.26; 95% CI: 2.42 - 7.5; p = 0.000), type of medication (adjusted OR: 0.35; 95% CI: 0.17 - 0.74; p = 0.006), and number of nurses serving medicine (adjusted OR: 0.45; 95% CI: 0.29 - 0.71; p = 0.000) were significantly associated with MAEs. Medication administration errors were not significantly associated with total number of patients in the ward, medication administration time, medication supply system, and day of observations. In Ali Abad Teaching, hospital 414 cases of medication administration were supervised, among those 164 cases (39.6%) were with erroneous administration. Wrong time error (61%) was the most frequent type of error, followed by missed dose (25.6%), compliance error (7.3%), with 8 errors (4.88%), which were reached to the patients and caused harm, but did not require interventions. Result of multivariate analysis shows that route of administration (adjusted OR: 6.82; 95 % CI: 4.11 - 11.31; p = 0.000) medication supply system (adjusted OR: 3.03; 95% CI: 1.76 - 5.2; p = 0.000) number of nurses serving medicine (adjusted OR: 0.37; 95% CI: 0.17 - 0.84; p = 0.016) and time of administration (adjusted OR: 4.17; 95% CI: 2.06 - 8.49; p = 0.000) were significantly associated with MAEs. The total number of patients in the ward, type of medication and day of observations were not significantly associated with MAEs. Based on the result of the Chi square test, number of medications was significantly associated with the number of errors in both hospitals (p < 0.05). The medication distribution system should be always updated, and all healthcare professionals should work together as an allied team to reduce incidences of MAEs. Thus, the unwanted consequences of MAEs will be prevented in patients and society.